Simplify by expressing fractional exponents instead of radicals
![Simplify by expressing fractional exponents instead of radicals class=](https://us-static.z-dn.net/files/d78/08774b37ef92389bcf03d1040a255cc2.png)
Answer:
[tex]a^{\frac{1}{2}}b^{\frac{1}{2}}[/tex]
Step-by-step explanation:
Given:
The expression in radical form is given as:
[tex]\sqrt{ab}[/tex]
We need to express this in fractional exponent form.
We know that,
[tex]\sqrt a=a^{\frac{1}{2}}[/tex]
Also, [tex]\sqrt{ab}=\sqrt a\times \sqrt b[/tex]
Now, clubbing both the properties of square root function, we can rewrite the given expression as:
[tex]\sqrt{ab}=\sqrt a \times \sqrt b\\\\\sqrt{ab}=a^{\frac{1}{2}}\times b^{\frac{1}{2}}\\\\\therefore \sqrt{ab}=a^{\frac{1}{2}}b^{\frac{1}{2}}[/tex]
So, the given expression in fractional exponents form is [tex]a^{\frac{1}{2}}b^{\frac{1}{2}}[/tex].
Answer:
ab = (ab)^(1/2)
Step-by-step explanation:
Odyssey ware